Analisis Kemampuan Pemecahan Masalah pada Materi Bangun Ruang Sisi Datar di Kelas IX - Pradita Unonongo; Sumarno Ismail; Kartin Usman (Jambura Journal of Mathematics Education, 2021)
This article discusses the problem-solving abilities of students in the flat-sided geometry material in the odd semester of the 2020/2021 school year. This research was conducted at SMP Negeri 2 Gorontalo involving 35 students of class IX as research subjects, who were selected using purposive sampling data collection techniques. Data collection was carried out using tests in the form of story questions to measure problem-solving abilities and interviews to strengthen and add the required information. Indicators used to measure problem-solving abilities include: 1) understanding the problem, 2) plan a solution, 3) solve the problem, 4) recheck the results obtained. The results showed that the average achievement of students' ability levels in solving contextual questions in class IX of SMP Negeri 2 Gorontalo was still in the low category, namely 53.51% although there were some students who got high scores. This is shown by the achievement of the indicator of understanding the problem with a percentage of 44.86%, the indicator of planning for completion getting a percentage of 61.14%, the indicator of solving the problem getting a percentage of 63.86% and the indicator re-checking the results obtained getting a percentage of 43.62%.